Academic success, engagement and self-efficacy of first-year university students: Personal variables and first-semester performance - Casanova, J. R. (2024)
Higher education can be hugely transformative for students and has an important role in empowering human capital, innovation, and society’s social, cultural, and environmental development. The expansion of higher education has promoted access for a more heterogeneous mix of students, but ensuring access does not guarantee academic success. This paper aims to analyse predictors of academic achievement in 447 first-year students in their 1st and 2nd semesters, considering variables including sex, age, parents’ educational level and grades on entering higher education, along with levels of students’ academic engagement and self-efficacy after some weeks at university. Results show statistically significant paths for sex, age, and GPA to 1st-semester achievement, for parent’s educational levels to perceived self-efficacy, for students’ academic engagement to 1st-semester achievement, and 1st-semester achievement to 2nd-semester achievement. Students’ academic engagement also had an indirect effect on the 2nd-semester achievement. The correlation between academic engagement and self-efficacy was positive, strong, and statistically significant. The model explained 35.2% of the variance in 2nd-semester achievement and 15.0% of the variance in 1st-semester achievement. Knowledge about predictors of academic achievement and the importance of engagement and self-efficacy will support timely interventions, promoting success and preventing failure and dropout.